Low priority of obesity education leads to lack of medical students’ preparedness to effectively treat patients with obesity: results from the U.S. medical school obesity education curriculum benchmark study - W. Scott Butsch; Robert F. Kushner; Susan Alford; B. Gabriel Smolarz (BMC Medical Education, 2020)
Abstract Background Physicians are currently unprepared to treat patients with obesity, which is of great concern given the obesity epidemic in the United States. This study sought to evaluate the current status of obesity education among U.S. medical schools, benchmarking the degree to which medical school curricula address competencies proposed by the Obesity Medicine Education Collaborative (OMEC). Methods Invitations to complete an online survey were sent via postal mail to 141 U.S. medical schools compiled from Association of American Medical Colleges. Medical school deans and curriculum staff knowledgeable about their medical school curriculum completed online surveys in the summer of 2018. Descriptive analyses were performed. Results Forty of 141 medical schools responded (28.4%) and completed the survey. Only 10.0% of respondents believe their students were “very prepared” to manage patients with obesity and one-third reported that their medical school had no obesity education program in place and no plans to develop one. Half of the medical schools surveyed reported that expanding obesity education was a low priority or not a priority. An average of 10 h was reported as dedicated to obesity education, but less than 40% of schools reported that any obesity-related topic was well covered (i.e., to a “great extent”). Medical students received an adequate education (defined as covered to at least “some extent”) on the topics of biology, physiology, epidemiology of obesity, obesity-related comorbidities, and evidence-based behavior change models to assess patient readiness for counseling (range: 79.5 to 94.9%). However, in approximately 30% of the schools surveyed, there was little or no education in nutrition and behavioral obesity interventions, on appropriate communication with patients with obesity, or pharmacotherapy. Lack of room in the curriculum was reported as the greatest barrier to incorporating obesity education. Conclusions Currently, U.S. medical schools are not adequately preparing their students to manage patients with obesity. Despite the obesity epidemic and high cost burden, medical schools are not prioritizing obesity in their curricula.